2023
DOI: 10.1021/acsomega.3c00290
|View full text |Cite
|
Sign up to set email alerts
|

Benchtop 19F Nuclear Magnetic Resonance (NMR) Spectroscopy Provides Mechanistic Insight into the Biginelli Condensation toward the Chemical Synthesis of Novel Trifluorinated Dihydro- and Tetrahydropyrimidinones as Antiproliferative Agents

Abstract: Benchtop nuclear magnetic resonance (NMR) spectroscopy has enabled the monitoring and optimization of chemical transformations while simultaneously providing kinetic, mechanistic, and structural insight into reaction pathways with quantitative precision. Moreover, benchtop NMR proton lock capabilities further allow for rapid and convenient monitoring of various organic reactions in real time, as the use of deuterated solvents is not required. The complementary role of 19F NMR-based kinetic monitoring in the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Very recently, Chen et al reported the synthesis of a diverse library of trifluoromethylated tetrahydropyrimidinone derivatives 412' via a one-pot three-component reaction of ethyl 4,4,4-trifluoro-3-oxobutanoate 1, thiourea 221, and para-and meta-substituted aryl aldehydes 138 in the presence of ytterbium(III) triflate catalyst in acetonitrile (Scheme 141). [239] Authors utilized benchtop 19 F NMR spectroscopy to probe the mechanism of the Biginelli cyclocondensation and the obtained results showed that the reaction follows the enamine mechanism, involving initial condensation of thiourea and β-ketoester.…”
Section: Putilova Et Al Reported the Use Of Ionic Liquid [Bmim][bfmentioning
confidence: 99%
“…Very recently, Chen et al reported the synthesis of a diverse library of trifluoromethylated tetrahydropyrimidinone derivatives 412' via a one-pot three-component reaction of ethyl 4,4,4-trifluoro-3-oxobutanoate 1, thiourea 221, and para-and meta-substituted aryl aldehydes 138 in the presence of ytterbium(III) triflate catalyst in acetonitrile (Scheme 141). [239] Authors utilized benchtop 19 F NMR spectroscopy to probe the mechanism of the Biginelli cyclocondensation and the obtained results showed that the reaction follows the enamine mechanism, involving initial condensation of thiourea and β-ketoester.…”
Section: Putilova Et Al Reported the Use Of Ionic Liquid [Bmim][bfmentioning
confidence: 99%
“…The crude reaction mixtures were directly analyzed by 19 F NMR. Reproduced with permission from ref . Copyright 2023 American Chemical Society.…”
Section: The Application Of Nmr To Drug Discovery Is In Constant Evol...mentioning
confidence: 99%
“…They have found uses for reaction monitoring, chemical analysis, and quantification and analysis of metabolite profiles among others. An inspection of recently published articles shows benchtop NMR data contributing to the quantification of oxidation products, 123 mechanistic insights of synthetic reactions (Figure 33), 124 cycloaddition reaction monitoring, 125 and complex biofluid mixture analysis. 126 Throughout this perspective, we see that numerous NMR workflows are underpinned by computational methods to accelerate data analysis.…”
Section: The Application Of Nmr To Drug Discovery Is In Constant Evol...mentioning
confidence: 99%